Culture and anomie in data sharing: a perspective from the researchers - Monteiro, Elizabete Cristina de Souza de Aguiar [UNESP]; Sant'Ana, Ricardo Cesar Goncalves [UNESP] (Pontificia Universidade Catolica Campinas, 2024)
The retention or release of data may vary according to the culture or prevailing values of a particular area of knowledge or practices adopted by individual researchers. Anomie can occur when there is an imbalance between institutional goals and cultural values, with greater relevance of collective or individual cultural values. In this way, researchers may disagree with institutional goals and engage in deviant behavior. The objective was point out clues of cultural influence on the state of anomie in researchers in the process of managing and sharing their data. Documentary, exploratory research, and the Content Analysis method were used with the application of a framework that considers the institutional and individual dimensions. The results pointed to indications that researchers have little clarity about institutional goals for data management and sharing. It is concluded that the possible anomie in the researchers' context is associated with the lack of knowledge or dubiousness about institutional, social, and moral norms, imbalance between goals and the ways to achieve them, noncompliance with institutional guidelines and poor data management skills.
Keywords: Anomie; Data sharing; Culture; Data management